Shift in phytoplankton community composition over fronts - Marina Lévy; Clément Haëck; Inès Mangolte; Angelina Cassianides; Roy El Hourany (Communications Earth & Environment)
Abstract Oceanic fronts often support enhanced phytoplankton biomass. Yet, how fronts influence the composition of phytoplankton communities remains poorly understood. Here, we leverage 18 years of high-resolution satellite data of sea-surface temperature and ocean color-derived pigments, converted into concentrations of seven phytoplankton groups, including diatoms, prokaryotes, and five other eukaryotic groups, to examine changes in phytoplankton community composition over fronts across oligotrophic to eutrophic conditions in the Northwest Atlantic. We found a population shift towards more diatoms and less prokaryotes at fronts, while the change in proportion of the other eukaryotic groups varies. This shift accounts for up to a half of the large-scale community dissimilarity, underscoring the substantial influence of fronts on phytoplankton community composition. Our findings suggest that fronts may serve as natural diatom refuges in a warming climate, highlighting the necessity of incorporating fine-scale oceanographic features like fronts into climate models.